Impact of systemic lupus erythematosus on cardiovascular morphologic and functional phenotypes: a Mendelian randomization analysis - Lin, Zishan; Wang, Wenfeng; Jiang, Bingjing; He, Jian; Xu, Yanfang (Frontiers in Cardiovascular Medicine, 2024)
Previous studies have established a correlation between systemic lupus erythematosus (SLE) and cardiovascular health, but the potential causal effects of SLE on heart function and structure remain poorly understood. Cardiovascular magnetic resonance (CMR) imaging, a novel non-invasive technique, provides a unique assessment of cardiovascular structure and function, making it an essential tool for evaluating the risk of heart disease. In this study, we performed a Mendelian randomization analysis to determine the causal relationship between SLE and CMR traits. Genetic variants independently linked to SLE were selected from a genome-wide association study (GWAS) containing 5,201 cases and 9,066 controls as instrumental variables. A set of 82 CMR traits was obtained from a recent GWAS, serving as preclinical indicators and providing preliminary insights into the morphology and function of the four cardiac chambers and two aortic segments. Primary analysis employed a two-sample Mendelian randomization study using the inverse-variance weighted method. Heterogeneity testing, sensitivity analyses, and instrumental variable strength assessments confirmed the robustness of the findings.SLE exhibited a correlation with increased stroke volume (βLVSV=0.007, P=0.045), regional peak circumferential strain (βEcc_AHA_9=0.013, P=0.002; βEcc_AHA_12=0.009, P=0.043; βEcc_AHA_14=0.013, P=0.006), and global peak circumferential strain of the LV (βEcc_global=0.010, P=0.022), as well as decreased regional radial strain (βErr_AHA_11=-0.010, P=0.017).This research presents evidence of a potential causal association between traits of SLE and alterations in cardiac function, guiding cardiac examinations and disease prevention in lupus patients.